Sagas in handwritten and printed books in 19th century Iceland - Davíð Ólafsson (Universität Tübingen, 2004)
As soon as the Icelandic sagas were first written on vellum in the 13th and 14th century, enthusiastic readers began to copy them and re-write for their own use and for further distribution. Little is known of the extent of this multiplication. However it is evident that popular stories were copied and distributed across the country in considerable number of copies shortly after they had been written. It is also clear that the tradition of copying and circulating manuscripts remained unbroken from the beginning of saga-writing in the middle ages beyond the development of printing technique in 16th century and all the way up to modern times. The immense number of manuscripts, preserved in national and local archives throughout Iceland, clearly indicates how people used their writing skills for communication and creation, collection and distribution. The vaults are filled with handwritten books, production and reproduction of literary and scholarly material such as traditional poetry and prose, rhymes, sagas and folktales, history and genealogy. Manuscripts were written, rewritten and copied, and sometimes printed books were copied in the same manner and distributed as handwritten books. Important part of this manuscript culture, which we can call the peoples´ press, is the copy and distribution of Icelandic medieval literature, stories of warriors and wise men, poets and politicians of the golden age of settlement and commonwealth. Comparison of printed and handwritten sagas in 18th and 19th century can shed some light on the function of Icelandic book market in the modern period where the handwritten book was the main channel.